Mechanische Herz-Kreislauf-Unterstützung bei akutem Rechtsherzversagen - Aziz, Saya; Dewald, Oliver; Tandler, Rene; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Right ventricular (RV) failure is associated with significant morbidity and mortality, with in-hospital mortality rates estimated to be as high as 70–75%. The RV failure can occur after cardiac surgery or isolated in certain situations, such as acute myocardial infarction, pulmonary embolism, left ventricular assist device implantation or after heart transplantation. Drug treatment includes fine tuning of the volume status and administration of inotropic agents, vasopressors and pulmonary vasodilators. Selected patients with persistent RV failure may benefit from mechanical circulatory support. Percutaneous and surgical mechanical support systems are increasingly being used. Systems for isolated RV support include percutaneous options, such as micro-axial flow pumps and extracorporeal centrifugal flow support devices as well as surgical options with RV support devices and arteriovenous extracorporeal membrane oxygenation. This review discusses the indications, patient selection, treatment strategies and outcomes of mechanical circulatory support for RV failure.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Acute right heart failure; Arteriovenous extracorporeal membrane oxygenation; Cardiogenic shock; Impella RP; Right ventricular assist devices